Integrin β1-mediated mast cell immune-surveillance of blood vessel content - Link, Kristina; Muhandes, Lina; Polikarpova, Anastasia; Lämmermann, Tim; Sixt, Michael; Fässler, Reinhard; Roers, Axel (The journal of allergy and clinical immunology, 2024)
Background - IgE-mediated degranulation of mast cells (MCs) provides rapid protection against environmental hazards, including animal venoms. A fraction of tissue-resident MCs intimately associates with blood vessels. These perivascular MCs were reported to extend projections into the vessel lumen and to be the first MCs to acquire intravenously injected IgE, suggesting that IgE loading of MCs depends on their vascular association. - Objective - We sought to elucidate the molecular basis of the MC-blood vessel interaction and to determine its relevance for IgE-mediated immune responses. - Methods - We selectively inactivated the Itgb1 gene, encoding the β1 chain of integrin adhesion molecules (ITGB1), in MCs by conditional gene targeting in mice. We analyzed skin MCs for blood vessel association, surface IgE density, and capability to bind circulating antibody specific for MC surface molecules, as well as in vivo responses to antigen administered via different routes. - Results - Lack of ITGB1 expression severely compromised MC-blood vessel association. ITGB1-deficient MCs showed normal densities of surface IgE but reduced binding of intravenously injected antibodies. While their capacity to degranulate in response to IgE ligation in vivo was unimpaired, anaphylactic responses to antigen circulating in the vasculature were largely abolished. - Conclusions - ITGB1-mediated association of MCs with blood vessels is key for MC immune surveillance of blood vessel content, but is dispensable for slow steady-state loading of endogenous IgE onto tissue-resident MCs.
Online verfügbar 16 April 2024, Version des Artikels 4 September 2024
Gesehen am 28.02.2025